Pengaruh Pemahaman Tata Tertib terhadap Kedisiplinan Santri di Pondok Pesantren Tanjung Resik At-Taqwa Kota Tasikmalaya - Halalah Amaliyah; M. Rifa Baihaqi; Imtyaz Nazifa Ainurrafiq; Shofin Muhammad; Bayu Adi Laksono (ISLAMIKA, 2023)
Islamic boarding schools are Islamic institutions that organize learning, deepen, practice Islamic law. The routine of the daily activities of the santri is in accordance with the existing regulations, this is intended to build self-discipline and self-discipline habits from the santri. This study aims to determine how high the effect of understanding the rules on the discipline of students. This study used a quantitative method with a total sample of 32 students at the Tanjung Resik At-Taqwa Islamic Boarding School, Tasikmalaya City. The research instrument uses a questionnaire filled out by respondents after conducting validity and reliability tests. The data analysis technique uses simple linear regression with the help of SPSS version 23. The results of data analysis are indicated by the t value on the disciplinary variable (Y) worth 6,756, while the Sig. of 0.000. indicated the value of Sig. < Alpha 0.05 then Ha is accepted, Adjusted R Square of 0.590 means that 59% of the contribution of the variable understanding of discipline (X) to discipline (Y) and 41% is not included in the model. While the correlation value in this study with R 0.777a shows a strong relationship between the variable understanding of discipline (X) and the variable discipline (Y). Thus it can be stated that the understanding of the rules affects the discipline of the students.